1994
DOI: 10.1111/j.1745-9125.1994.tb01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Routes to Delinquency: Differences Between Early and Late Starters in the Impact of Parenting and Deviant Peers*

Abstract: This paper tests hypotheses concerning differences in the determinants of involvement with the criminal justice system for adolescents who show early versus late onset of delinquency. Four waves of data collected on 177 adolescent boys living in small towns in the midwest were used to test the hypotheses. For late starters, quality of parenting predicted affiliation with deviant peers, which was associated in turn with criminal justice system involvement. Oppositional/defiant behavior was unrelated both to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
2
10

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(182 citation statements)
references
References 32 publications
9
161
2
10
Order By: Relevance
“…The court can also order "open" detention, allowing DJJ to make the decision based on available bed space and their assessment of risk. Between court dates, detention xxiii Delinquent peer and family influences have been found to be predictive of youth delinquency in general (Elliott & Menard 1996;Farrington 1995;Keenan et al 1995;Simons et al 1994;Wasserman et al 2003).…”
Section: Chaptermentioning
confidence: 99%
“…The court can also order "open" detention, allowing DJJ to make the decision based on available bed space and their assessment of risk. Between court dates, detention xxiii Delinquent peer and family influences have been found to be predictive of youth delinquency in general (Elliott & Menard 1996;Farrington 1995;Keenan et al 1995;Simons et al 1994;Wasserman et al 2003).…”
Section: Chaptermentioning
confidence: 99%
“…Relationships with antisocial peers are associated with the emergence of externalizing behavior (Elliott, Huizinga, & Ageton, 1985;Laird, Jordan, Dodge, Pettit, & Bates, 2001;Lansford, Criss, Pettit, Dodge, & Bates, 2003;Simons, Wu, Conger, & Lorenz, 1994), especially when these relationships are close friendships (Huey, Henggeler, Brondino, & Pickrel, 2000;Laird, Pettit, Dodge, & Bates, 1999;Morgan & Grube, 1991). This association may result both from friends' deviance causing increased antisocial behavior and one's own externalizing behavior tendencies resulting in the formation of deviant friendships (Deater-Deckard, 2001).…”
Section: Friend Deviancementioning
confidence: 99%
“…Critical reviews of empirical research have indicated that rejection by one's peer group in childhood is associated with later maladjustment, especially externalizing behavior problems (Kupersmidt, Coie, & Dodge, 1990;Parker & Asher, 1987). Moreover, being rejected by one's peer group in middle childhood has been linked to subsequent involvement with antisocial peers during adolescence (e.g., Coie, Terry, Zakriski, & Lochman, 1995;Dishion, Patterson, Stoolmiller, & Skinner, 1991), which also has been identified as a correlate and possible precursor to antisocial outcomes (e.g., Simons, Wu, Conger, & Lorenz, 1994). However, it is unclear whether unsuccessful peer relationships during childhood and involvement with antisocial peers during adolescence represent successive stages of progression toward delinquency and criminality (Patterson, 1982), whether some characteristic or attribute of the individual underlies developmentally changing expressions of social maladaptation (Moffitt, 1993), or whether social rejection and deviant peer involvement represent different pathways to antisocial behavior.…”
mentioning
confidence: 99%